The Evolution of Private Label Brands and the Adoption of Sustainability Concepts in Thailand’s Retail Landscape - Daengrasmisopon, Thittapong (International Journal of Development Administration Research, 2026)
This study analyzes the development of private label (PL) brands and the growing incorporation of sustainability principles in Thailand’s retail industry. Traditionally regarded as inexpensive substitutes for national brands, private labels have evolved into strategically distinct products marked by superior quality, innovation, and brand equity. This article conducts an analysis of the primary factors facilitating this change, based on an extensive review of academic literature, industry reports, and empirical data, including regulatory frameworks, evolving consumer behavior, and innovations in supply chain processes. Special emphasis is placed on the Thai retail environment as an emerging market, where sustainability has increasingly become a vital element of private label strategy. The results indicate that although consumer awareness of sustainability is increasing, real purchase behavior is limited by reasons including price sensitivity, perceived risk, and skepticism regarding sustainability assertions. The study highlights the importance of institutional support, technical innovation, and collaborative supply chain networks in advancing the creation of sustainable private label companies. This report enhances the literature by offering a comprehensive perspective on the various elements influencing sustained private label development in emerging economies. It also suggests avenues for future research, namely in examining culturally distinct consumption habits, the urban-rural split, and the impact of developing technology on improving transparency and customer participation. The report highlights sustainability as a vital strategic differentiation for private label businesses in Thailand’s changing retail environment.